2017
DOI: 10.1002/ajmg.a.38416
|View full text |Cite
|
Sign up to set email alerts
|

Challenges in measuring the effects of pharmacological interventions on cognitive and adaptive functioning in individuals with Down syndrome: A systematic review

Abstract: We systematically reviewed the measures used in pharmaceutical trials in children/adults with Down syndrome without dementia. Our purpose was to identify developmentally appropriate outcome measures capable of detecting changes in cognitive and adaptive functioning in this population. Eleven studies were included and used diverse outcome measures across the domains of language, memory, attention, behavior, and executive/adaptive functioning. Our results highlight the challenges in selecting measures capable of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…Translating these anatomical and neural findings has helped refine what aspects of cognition are targeted in studies of individuals with Down syndrome. Specific constructs of executive functioning, learning and memory, and working memory are being targeted with an emphasis on determining the best measures for assessing these constructs and change in these constructs [12][13][14][15][16]. Further attention to the measurement of cognitive constructs has focused on social cognition, emotion recognition, and evaluating cognitive batteries [17][18][19][20][21][22][23][24][25][26][27][28].…”
Section: Cognitive Development and Independencementioning
confidence: 99%
“…Translating these anatomical and neural findings has helped refine what aspects of cognition are targeted in studies of individuals with Down syndrome. Specific constructs of executive functioning, learning and memory, and working memory are being targeted with an emphasis on determining the best measures for assessing these constructs and change in these constructs [12][13][14][15][16]. Further attention to the measurement of cognitive constructs has focused on social cognition, emotion recognition, and evaluating cognitive batteries [17][18][19][20][21][22][23][24][25][26][27][28].…”
Section: Cognitive Development and Independencementioning
confidence: 99%
“…Existing measures often lack reliability, can be insensitive to change among individuals with Down syndrome, and may not be suitable for repeated assessment (See Edgin et al, 2017;Esbensen et al, 2017, & Keeling et al, 2017 for overviews). Esbensen et al (2017) suggested that the BRIEF (parent/caregiver report measure) has adequate test-retest reliability among individuals with Down syndrome (see also D' Ardhuy et al, 2015).…”
Section: Existing Executive Function Tasks Used With Adults With Downmentioning
confidence: 99%
“…However, no clinical trials to date have demonstrated significant benefits in these domains in individuals with DS. A recent randomized double‐blind, placebo‐controlled trial of rivastigmine in children and adolescents with DS suggested potential improvement in a subset of participants for expressive language, but overall was not associated with significant effects on adaptive function, executive function, language or memory measures (Keeling et al, in press; Spiridigliozzi et al, ). A major challenge noted in these studies has been the choice of neurocognitive measures that are sensitive to change in cognition and overall function, as many of the measures used have been standardized for a neurotypically developing population or may be associated with ceiling or floor effects in the study population with DS (Heller, Spiridigliozzi, Crissman, Sullivan‐Saarela, Li, et al, ).…”
Section: Clinical Trials In Down Syndromementioning
confidence: 99%